ISLAM DAN TRADISI JAWA: Pencarian Motif Dan Makna Dalam Tradisi Selametan Mendirikan Rumah Di Dusun Gentan Ngrupit Jenangan Ponorogo - Miftahul Huda Huda (Dialogia: Islamic Studies and Social Journal, 2016)
Abstract:  Encountering between Islam and Javanese culture is fascinating to study. It is proved by cultural unique in Java community, such “selametan” tradition in building the house. Therefore, in this study discover two elements. First, look for the motivation in holding that tradition.  Second, the depth meaning of “selamatan sajen” towards Javanese community. This study conducted qualitative approach and this was case study. This study focused on the relation between Islam Javanese culture. The population was the civilizing of Gentan, Ngrupit, Jenangan, Ponorogo. Observation and interview were used to collect the data. It was found that the existence of selametan sajen is as same as the Islamic assent. It was proved by Prophet Adam a.s and his son also used that tradition in the past. Moreover, the intended meaning of its culture is to pray to Allah. Then the purposes are, first, safeness during the process in building house; second, hopefully neighbors blessing. Selamatan tradition invites their neighborhood and gives them various kinds of food and snacks. Those are called as sajen. In line, selametan tradition such building a house, has contribution in spiritual education. As the reason, its sajen has different depth meaning of each symbol. And it can be seen in Islamic culture. Keywords: Mbah Pujonggo, Singkretis, Nayuh, Kembang Setaman.